Family Firms That Care: CSR’s Hidden Path to Performance - Sukiantono Tang; Sheila Septiany; Budi Harsono; Serly Serly; Azan Khoh (Politeknik Ganesha Medan, 2025)
This study examines the effectiveness of Corporate Social Responsibility (CSR) in improving employee commitment and organizational performance, focusing on its role as a psychological strategy. Many companies are reluctant to implement CSR because they believe it has no direct effect on performance, especially since factors such as organizational identification and commitment are difficult to measure. The research uses a quantitative approach with primary data collected through an online survey of employees from family firms in Batam. The population consists of all employees of family firms in the area, with purposive sampling producing 211 respondents. Data analysis employed the Partial Least Squares (PLS) method using SmartPLS software. The results show that CSR toward employees and CSR toward the environment significantly improve organizational performance through partial mediation by organizational commitment and organizational identification. CSR toward employees has the strongest mediation effect through organizational commitment, while CSR toward the environment shows partial mediation through organizational identification. CSR toward the community has weak or no mediation effects. The findings indicate that CSR programs focusing on employees and the environment are more effective in enhancing performance by strengthening employee identification and commitment. For management, this suggests designing CSR initiatives that involve employees directly. The results also offer guidance for educational institutions and policymakers in creating more contextual human resource and CSR programs. This research contributes to understanding the psychological mechanisms linking CSR and performance through sequential mediation of organizational identification and commitment, an area that remains underexplored in family firms in emerging economies. This study extends CSR research by introducing sequential mediation of organizational identification and commitment in family firms in emerging economies, a mechanism rarely examined in prior studies